MOOC Developers’ Motivation - Tengku Sharif, Tengku Intan Suzila; Mohamad Noor, Mohd Yusri; Omar, Siti Rohana (UPENA Pahang, 2021)
Massive Open Online Courses (MOOC) has become more relevant during this Covid-19 pandemic. MOOC enables students to learn generic courses by sharing platforms between universities with similar curriculum and study plans. These common courses may pose different challenges to students as their universities’ standards varies although they are of shared credits. The challenge includes the developers’ motivation. This paper presents a study on how students’ acceptance and satisfaction of one such generic MOOC course, i.e. Ethnic Relations, reflects the MOOC developers’ motivation during preparation of the lessons. Questionnaires were distributed to 93 students who enrolled in this subject. The objectives are to unfold factors that are demanded in the course development and how the students’ expectations mirror the developers’ motivation. This study suggests that developers have to tackle an increasing dissatisfaction of the contents. The need for developers to be persistent until the end in completing the course development is mandatory. Insufficient and poorly constructed teaching materials in MOOC would only harm the learning process. Interest in the subject matter and supports may assist MOOC developers to produce well-developed student centered courses.